Ancient Human Genomes and Environmental DNA from the Cement Attaching 2, 000-Year-Old Head Lice Nits. (28th December 2021) - Pedersen, Mikkel W; Antunes, Catia; De Cahsan, Binia; Moreno-Mayar, J Víctor; Sikora, Martin; Vinner, Lasse; Mann, Darren; Klimov, Pavel B; Black, Stuart; Michieli, Catalina Teresa; Braig, Henk R; Perotti, M Alejandra
Abstract: Over the past few decades, there has been a growing demand for genome analysis of ancient human remains. Destructive sampling is increasingly difficult to obtain for ethical reasons, and standard methods of breaking the skull to access the petrous bone or sampling remaining teeth are often forbidden for curatorial reasons. However, most ancient humans carried head lice and their eggs abound in historical hair specimens. Here we show that host DNA is protected by the cement that glues head lice nits to the hair of ancient Argentinian mummies, 1, 500–2, 000 years old. The genetic affinities deciphered from genome-wide analyses of this DNA inform that this population migrated from north-west Amazonia to the Andes of central-west Argentina; a result confirmed using the mitochondria of the host lice. The cement preserves ancient environmental DNA of the skin, including the earliest recorded case of Merkel cell polyomavirus. We found that the percentage of human DNA obtained from nit cement equals human DNA obtained from the tooth, yield 2-fold compared with a petrous bone, and 4-fold to a bloodmeal of adult lice a millennium younger. In metric studies of sheaths, the length of the cement negatively correlates with the age of the specimens, whereas hair linear distance between nit and scalp informs about the environmental conditions at the time before death. Ectoparasitic lice sheaths can offer an alternative, nondestructive source of high-quality ancient DNA from a variety of host taxa where bones and teeth are not available and reveal complementary details of their history.